Characterisation of the xylem of 352 conifers - Garcia Esteban, L.=700 1 De Palacios de Palacios, P.; Guindeo Casasus, A.; Garcia Fernandez, F.
(Es, En)
ilus., 14 ref.
Keywords: CONIFERALES; ANATOMIA DE LA MADERA; XILEMA; MADERA; ESPAÑA